Investigating the interrelationships among food habits, sports nutrition knowledge, and perceived barriers to healthy eating: a study of adolescent swimmers - AlKasasbeh, Walaa; Akroush, Sofia (Frontiers in Nutrition, 2024)
This cross-sectional study aims to explore the relationships between food habits, perceived barriers to healthy eating, and sports nutrition knowledge among adolescent swimmers. The study focuses on understanding how these factors interact and influence dietary choices in young athletes. A cohort of 52 adolescent swimmers aged 12–18 from Al Hussein Youth Club in Al-Hussein Sport City participated in the study. Data were collected through surveys assessing food habits, perceived barriers to healthy eating, and sports nutrition knowledge. Pearson Correlation analysis was employed to examine associations between variables, and stepwise regression analysis was used to identify predictors of food habits. The analysis revealed a significant positive association between food habits and sports nutrition knowledge (r = 0.393, p = 0.004). Knowledge emerged as a significant positive predictor of food habits (β = 0.393, p = 0.004), highlighting the influential role of sports nutrition knowledge in shaping the dietary choices of adolescent swimmers. However, the introduction of Barriers lacked significance, and individual predictors did not reach statistical significance. These findings underscore the importance of targeted interventions aimed at enhancing nutritional education among adolescent swimmers. Understanding the interplay between knowledge, barriers, and food habits provides valuable insights into the complex dynamics that influence the dietary choices of young athletes. Addressing these factors through tailored educational programs can promote healthier eating habits and optimize performance among adolescent swimmers. This study highlights the critical role of sports nutrition knowledge in shaping the dietary behaviors of adolescent swimmers. By addressing knowledge gaps and overcoming perceived barriers, targeted interventions can help improve food habits and enhance the overall health and performance of young athletes.